1986
DOI: 10.1071/bi9860193
|View full text |Cite
|
Sign up to set email alerts
|

The Movement of Fluids and Substances in the Testis

Abstract: Three aspects of the control of movements of fluids and substances into, out of and inside the testis are discussed: the tubular barrier, the interstitial extracellular fluid and the testicular blood vessels. The functional basis for the tubular barrier is twofold; there are significant differences in the concentration of many substances inside and outside the tubules and marker substances enter or leave the tubular fluid at widely different rates, depending on lipid solubility and the presence of specific car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 34 publications
3
25
1
Order By: Relevance
“…The relative volume of blood and lymph vessels was not affected by diet in the study by Hö tzel et al (1998), but their absolute volumes increased or decreased as a function of the change in testicular size. These changes in the vasculature and the associated changes in blood flow, accommodate the transport of testosterone to the peripheral circulation (Setchell, 1986 and1990). Thus, the present data are in agreement with a previous nutritional study in mature rams (Setchell et al, 1965) and suggest that total blood flow was affected while there was probably little or no change in blood flow per unit mass of testis.…”
Section: Nutritional Effects On Testicular Interstitial Tissuessupporting
confidence: 92%
“…The relative volume of blood and lymph vessels was not affected by diet in the study by Hö tzel et al (1998), but their absolute volumes increased or decreased as a function of the change in testicular size. These changes in the vasculature and the associated changes in blood flow, accommodate the transport of testosterone to the peripheral circulation (Setchell, 1986 and1990). Thus, the present data are in agreement with a previous nutritional study in mature rams (Setchell et al, 1965) and suggest that total blood flow was affected while there was probably little or no change in blood flow per unit mass of testis.…”
Section: Nutritional Effects On Testicular Interstitial Tissuessupporting
confidence: 92%
“…Furthermore, the data are consistent with the observation that the size of the lumen continues to enlarge well beyond the onset of spermatogenesis and pubertythat is, up to the 60th day after birth in rats (Tindall et al, 1975). As pointed out by Setchell(1986), a progressive and delayed development of the barrier is further supported by the finding that the concentration of androgen binding protein (ABP) in the epididymis-"a biochemical marker of formation of the barrier"-also continues to rise beyond the onset of spermatogenesis (Tindall et al, 1975). These observations suggest that fluid secretion by Sertoli cells may be related to the competence of the barrier.…”
Section: Introductionsupporting
confidence: 90%
“…The columnar and convoluted structure of Sertoli cells provides physical support for spermatogonia undergoing mitosis, spermatocytes undergoing meiosis, and spermatids undergoing spermatogenesis to become spermatozoa (35). Sertoli cell-mediated environmental interactions are essential in the creation of the blood-testis barrier and maintenance of the unique microenvironment within the seminiferous tubule required for germ cell development (36). However, an earlier study showed that in vitro cultured Sertoli cells were unable to fully respond to some treatments, including androgen (37).…”
Section: Discussionmentioning
confidence: 99%